Religiusitas Sebagai Moderator Pengaruh Stres Kerja Terhadap Psychological Well-being Pada Guru TK - Rufiati, Alfina; Pratiwi, Dewi (UIN Sultan Maulana Hasanudin Banten, 2025)
This research aims to determine whether there is an effect of work stress on psychological well-being, and whether religiosity can be a moderating variable in the influence of the two variables. This research uses a quantitative approach with a moderation regression analysis technique. The population used in this study were kindergarten teachers. The sample taken using the cluster random sampling technique was 291. This research uses several classical assumption tests such as normality tests, multicollinearity tests, heteroscedasticity tests, and hypothesis tests using moderation regression analysis. The results of the hypothesis test are that work stress has a significant negative effect on psychological well-being. So the higher the work stress a kindergarten teacher has, the lower their psychological well-being. This research also explains that religiosity can significantly be a moderator variable by weakening the influence of work stress on psychological well-being. So the more religiosity increases, the more work stress decreases, and psychological well-being will increase.